A prognostic score including mutation profile and clinical features for patients with CMML undergoing stem cell transplantation - Gagelmann, Nico; Badbaran, Anita; Beelen, Dietrich W.; Salit, Rachel B.; Stölzel, Friedrich; Rautenberg, Christina; Becker, Heiko; Radujković, Aleksandar; Panagiota, Victoria; Bogdanov, Rashit; Christopeit, Maximilian; Park, Yong; et al. (Blood advances, 2021)
The inclusion of mutation status improved risk stratification for newly diagnosed patients with chronic myelomonocytic leukemia (CMML). Stem cell transplantation is a potentially curative treatment option, and patient selection is critical because of relevant transplant-related morbidity and mortality. We aimed to evaluate the impact of mutation status together with clinical presentations on posttransplant outcome. Our study included 240 patients with a median follow-up of 5.5 years. A significant association with worse survival was identified for the presence of mutations in ASXL1 and/or NRAS. In multivariable analysis, ASXL1- and/or NRAS-mutated genotype (hazard ratio [HR], 1.63), marrow blasts >2% (HR, 1.70), and increasing comorbidity index (continuous HR, 1.16) were independently associated with worse survival. A prognostic score (CMML transplant score) was developed, and the following points were assigned: 4 points for an ASXL1- and/or NRAS-mutated genotype or blasts >2% and 1 point each for an increase of 1 in the comorbidity index. The CMML transplant score (range, 0-20) was predictive of survival and nonrelapse mortality (P < .001 for both). Up to 5 risk groups were identified, showing 5-year survival of 81% for a score of 0 to 1, 49% for a score of 2 to 4, 43% for a score of 5 to 7, 31% for a score of 8 to 10, and 19% for a score >10. The score retained performance after validation (concordance index, 0.68) and good accuracy after calibration. Predictions were superior compared with existing scores designed for the nontransplant setting, which resulted in significant risk reclassification. This CMML transplant score, which incorporated mutation and clinical information, was prognostic in patients specifically undergoing transplantation and may facilitate personalized counseling.
Gesehen am 18.07.2021